2017
DOI: 10.1037/apl0000204
|View full text |Cite
|
Sign up to set email alerts
|

Motivated cognition and fairness: Insights, integration, and creating a path forward.

Abstract: How do individuals form fairness perceptions? This question has been central to the fairness literature since its inception, sparking a plethora of theories and a burgeoning volume of research. To date, the answer to this question has been predicated on the assumption that fairness perceptions are subjective (i.e., "in the eye of the beholder"). This assumption is shared with motivated cognition approaches, which highlight the subjective nature of perceptions and the importance of viewing individuals arriving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 155 publications
(241 reference statements)
3
79
0
Order By: Relevance
“…Second, our research highlights the role of transgressor motives in shaping their perceptions of the reconciliation process. Our findings are consistent with the body of research on motivated cognition, which demonstrates that people's perceptions of others can be filtered through their motives, leading them to interpret targets in ways that support desired conclusions (Barclay et al, ; Huang & Bargh, ; Kunda, ). Interpersonal transgressions are inherently ambiguous events in which the parties may have differing views, and forgiveness must be inferred by transgressors because it is a process occurring within the victim.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Second, our research highlights the role of transgressor motives in shaping their perceptions of the reconciliation process. Our findings are consistent with the body of research on motivated cognition, which demonstrates that people's perceptions of others can be filtered through their motives, leading them to interpret targets in ways that support desired conclusions (Barclay et al, ; Huang & Bargh, ; Kunda, ). Interpersonal transgressions are inherently ambiguous events in which the parties may have differing views, and forgiveness must be inferred by transgressors because it is a process occurring within the victim.…”
Section: Discussionsupporting
confidence: 89%
“…Motivated cognition refers to the general process by which people's preferences, expectations, and motives influence their interpretation of events (Barclay et al, 2017;Kunda, 1990;Sonenshein, 2007). According to the reconfiguration principle of motivated cognition, motives direct people's attention toward information that confirms their desired outcomes and away from disconfirming information (Huang & Bargh, 2014).…”
Section: Study 3: Apology Motives and Transgressor Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the existing evidence in case of procedural justice makes this an unlikely proposition. Several cognitive psychological studies have shown that the perception of procedural justice is a fundamental psychological process ('fairness heuristic', see Barclay et al 2017;Lind 2001;Proudfoot and Lind 2015), whilst relational identification (i.e., social identity) and constructs that require deliberation (i.e., legitimacy) are more complex (Barclay et al 2017;van Lier et al 2013;Tabibnia et al 2008). Although this line of reasoning might be alien to criminological audiences, in the psychological literature it is widely accepted that more basic psychological processes are affecting (and informing) more complex ones down the line (Von Hippel et al 2005;Kahneman 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we see high potential in researching the role of fairness in open innovation. Ample evidence and theorizing from the field of psychology indicate that actors compare their derived value with the value derived by other actors in the same system (Barclay, Bashshur, and Fortin, 2017). This comparison forms the basis of fairness perceptions, which have affective, cognitive, and behavioral consequences (Barclay et al, 2017).…”
Section: Value Realizationmentioning
confidence: 99%